The Effect of Principal’s Supervision on Teachers’ Performance - Harahap, Muhammad Junaidi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Education basically aims to develop the abilities possessed by humans. Therefore, schools are a good place to develop these abilities to achieve educational goals. The role of each element of the school is important. The principal, as the highest leader, assisted by teachers and staff, has an active role, including carrying out supervision activities aimed at improving teachers’ performance in the learning process. Teachers are the main role in realizing the expected goals. This study aims to analyze the effect of principal supervision on teachers’ performance. This study is a correlational study with a quantitative research type. The population in this study was all teachers of SMA PGRI Babat Toman in Musi Banyuasin Regency. Because the population is less than 100, all populations are used as research samples so that this study is known as total sampling. The instruments used consisted of supervision questionnaires and teachers’ performance. Based on the results of the study, it shows that academic supervision is one way that can be done by the principal in the context of coaching and mentoring teachers to improve teacher quality. The results of the significance test show that there is a positive influence of principal supervision on the performance of high school teachers. Through the results of this study, it can be used as a means for schools to carry out academic supervision routinely and continuously to control the quality of teachers in the learning process.